Health‐Related Influences of Extending Marital Benefits to Same‐Sex Couples: Results From the California Health Interview Survey. Issue 5 (10th October 2020) - Elwood, William N.; Irvin, Veronica L.; Liu, Benmei; Lee, Richard; Breen, Nancy
Abstract : Objective: To explore how incremental California legal changes toward the implementation of same‐sex marriage influenced self‐reported mental and physical health among adult Californians in legal same‐sex marriages and partnerships. Methods: We analyzed California Health Interview Survey data from 2005 to 2015 to assess the relationship between self‐reported mental and physical health and legal same‐sex marital/partnership status. Physical health was measured using a single self‐report question, mental health using the six‐item Kessler distress scale. Independent variables were sexual identity and legal marital/partner status. Bivariate analyses compared mental and physical health before and after the 2008 California Supreme Court decision affirming marriages as a basic civil or human right. Multivariate analyses tested relationships between marital/partnered status, sexual identity by year after adjusting for sociodemographics. Results: Reports of poor and fair health decreased, reports of very good health increased, and psychological distress scores decreased for legally coupled gay men and lesbians but increased slightly for single lesbians and gay men. Household income increased among espoused lesbians and gay men and decreased among unmarried counterparts. Conclusions: Espoused gay and lesbian respondents were more likely to be employed and to have college educations than unmarried counterparts, perhaps a continuing influence of 2005 California legislation requiring private employers to provide health insurance benefits to employees' same‐sex partners. Our findings suggest that physical and mental health improved for lesbians and gay men once same‐sex marriage became legal throughout California. Implications: These findings demonstrate a need for survey questions to elicit information about marital status and the sex/gender of a respondent's spouse inclusive of sexual and gender identities.